Impact of Teaching Experience on Teachers Attitude towards the Use of Instructional Television (ITV) in Bayelsa State Nigeria - Bridget, Nemine, Ebi-Bulami; Akintunde, Akinbowale Olakunle (Asian Journal of Education and Training, 2019)
The main thrust of this study is to find out the teachers’ attitude generally toward instruction television (ITV), also to find out the impact of length of work experience on its use. This survey study was carried out in selected secondary in Ekeremor LGA of Bayelsa State. The mann-whitney U test was used in the analysis because it is based on ordinal scale intervals. On the general attitude of teachers towards the use of instructional television, the smaller U (47) is higher than the critical U is (2.3) the null hypothesis was rejected and retained the alternate hypothesis of there is no significant difference in attitude and secondary school teacher towards the use of (ITV). Also, the use of ITV based and the length of teaching experience, the computed U value (32) and the smaller U is (3.0), the null hypothesis was rejected and retained the alternate hypothesis of there is no significant difference in attitude among secondary teachers with different length of teaching experience towards the use of instruction television in Ekeremor L.G.A of Bayelsa State Nigeria. The study portrayed that they have a favorable disposition towards the use of ITV and it was recommended that some television stations should broadcast well tutored and design suitable lesson to learners.